2016
DOI: 10.1007/s12307-016-0180-7
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietins Modulate Survival, Migration, and the Components of the Ang-Tie2 Pathway of Chronic Lymphocytic Leukaemia (CLL) Cells In Vitro

Abstract: In actuality, chronic lymphocytic leukaemia (CLL) remains an incurable haematopoietic malignancy of high prevalence amongst elderly populations in the West.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…In this study, we show ANGPT2 was significantly elevated in NI patients compared to healthy controls and, although it was higher in NP patient plasma compared to controls, this did not reach significance. It is of interest that ANGPT2 is a key player in the ANGPT2-Tie2 pro-angiogenic pathway and also in the metabolic fitness of a number of cells 55 . Since we found that both angiogenesis and mitochondrial activity were higher in NI ECFCs compared to the NP, these data correlated with the elevated levels of ANGPT2 that were detected in the NI vs NP cells.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we show ANGPT2 was significantly elevated in NI patients compared to healthy controls and, although it was higher in NP patient plasma compared to controls, this did not reach significance. It is of interest that ANGPT2 is a key player in the ANGPT2-Tie2 pro-angiogenic pathway and also in the metabolic fitness of a number of cells 55 . Since we found that both angiogenesis and mitochondrial activity were higher in NI ECFCs compared to the NP, these data correlated with the elevated levels of ANGPT2 that were detected in the NI vs NP cells.…”
Section: Discussionmentioning
confidence: 99%
“…This is not altogether surprising considering the stimulation of angiogenesis is probably the key role of TEM [ 3 , 5 , 9 ]. The importance of the process has been described not only in the development of solid tumors but also in the pathomechanism of lymphoproliferative tumors, including CLL [ 32 , 33 , 34 ]. CLL patients demonstrate increased vascularization density of lymph nodes [ 32 ] and bone marrow [ 33 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, it is widely recognized that angiogenesis promotes the proliferation of malignant cells in CLL [43]; however, the molecular mechanisms of this process are still poorly understood. Tumor substrate cells in CLL produce a large number of angiogenic factors, thus stimulating angiogenesis [44]. Excessive expression of these factors leads to microenvironmental dysfunction, supports proliferation of malignant B-lymphocytes and increases their resistance to apoptosis.…”
Section: Relationship Between Pathological Angiogenesis and Vegf Levelmentioning
confidence: 99%
“…Some publications describe that natural killer (NK) cells produce various proangiogenic factors in humans and mice [57], such as VEGF and PIGF, which can significantly accelerate tumor growth [58]. In patients suffering from CLL, it was shown that tumor clone cells produce angiogenic factors, including VEGF, stimulating cell proliferation [43,44].…”
Section: Relationship Between Pathological Angiogenesis and Vegf Levelmentioning
confidence: 99%